The Optimization of Image Processing Algorithms for Eye Movement Recording - Daunys, G.; Laurutis, V. (Elektronika ir Elektrotechnika, 1999)
The mathematical model for eye movement recording system, which utilize corneal reflection displacement relative to the center of the pupil, was developed. The model describes distortion of image. The algorithm for pupil center tracking was developed. The method for determining angular eye position presented.